2017
DOI: 10.1007/s10067-017-3936-7
|View full text |Cite|
|
Sign up to set email alerts
|

First clinical symptom as a prognostic factor in systemic sclerosis: results of a retrospective nationwide cohort study

Abstract: The objective of the study is to determine the importance of the mode of onset as prognostic factor in systemic sclerosis (SSc). Data were collected from the Spanish Scleroderma Registry (RESCLE), a nationwide retrospective multicenter database created in 2006. As first symptom, we included Raynaud's phenomenon (RP), cutaneous sclerosis, arthralgia/arthritis, puffy hands, interstitial lung disease (ILD), pulmonary arterial hypertension (PAH), and digestive hypomotility. A total of 1625 patients were recruited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…This is also in agreement with the relatively rare use of immunosuppressive drugs in patients with later disease onset; however, the fact that elderly patients are more vulnerable to risks of immunosuppressive therapies, especially to infections and malignancies, and that physicians might be more reluctant to prescribe immunosuppressive drugs in the elderly might also contribute to this observation. Our data support the suggestion of several other studies to use the older age at disease onset as an independent prognostic factor, together with the diffuse subset, lung involvement, PH and renal crisis [ 10 , 26 , 27 ] for a poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is also in agreement with the relatively rare use of immunosuppressive drugs in patients with later disease onset; however, the fact that elderly patients are more vulnerable to risks of immunosuppressive therapies, especially to infections and malignancies, and that physicians might be more reluctant to prescribe immunosuppressive drugs in the elderly might also contribute to this observation. Our data support the suggestion of several other studies to use the older age at disease onset as an independent prognostic factor, together with the diffuse subset, lung involvement, PH and renal crisis [ 10 , 26 , 27 ] for a poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…It should also be mentioned that in a retrospective study it was shown that digital amputation was associated with older age, long history of RP, long disease duration and presence of anticentromere antibody. This could probably be explained by the coexistence of other micro/macrovascular disease processes [ 26 ]. Our observation that vasculopathic organ manifestations, except digital ulcers, were more common in the late onset cohort, and inflammatory symptoms more frequent in the early onset cohort support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The individual analysis of CRP courses revealed two extreme subpopulations characterized by consistent CRP elevations (inflammatory SSc) or CRP values in the normal range (non-inflammatory SSc). Parameters found to be more common in the inflammatory group, such as pulmonary fibrosis, cardiac arrhythmia, dcSSc, higher mRSS, reduced lung function, the presence of anti-Scl-70 antibodies, or higher age, are associated with increased mortality [14][15][16][17][18]. Moreover, the proportion of male gender, which has been linked to increased mortality in SSc [14,15,19], was higher in the inflammatory subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…ILD is an early complication in SSc, and in some patients (approximately 4%) the first clinical symptom of SSc is directly related to ILD [2,14]. Most patients who develop severe restrictive lung disease do so in the first 5 years following the onset of SSc symptoms [2].…”
Section: Introductionmentioning
confidence: 99%